P174 System delays have real consequences: Impact of timing of biologic commencement on inflammatory bowel disease patient response. (25th January 2019) - McCulloch, A; Abbas, M; Bannaga, A; McDowell, P; Bate, T; Kandathil, M; Shah, J; Sharif, Q; Love, M; Sharma, N; Cooney, R
Abstract: Background: The worldwide incidence and prevalence of inflammatory bowel disease (IBD) is increasing and with this the need for biologic therapy continues to rise. This inevitably strains the finite resources of public health services. We examined our cohort of IBD patients to determine whether the wait for biologic therapy impacted overall outcomes. Methods: This was a single-centre retrospective review of adult patients with IBD who had been commenced on a biological therapy from January 2009 to October 2017. Inclusion criteria included patients with IBD who had started biologics as an outpatient. We excluded patients who had been started on biologics as an inpatient or had been admitted to hospital in the 3 months prior to starting biologics. Patients that met the inclusion criteria were divided into an early group, that is, those receiving biologics within 40 days of multidisciplinary team (MDT) approval; and a late group, that is, those patients receiving biologics over 40 days from MDT approval. Outcome measures were 1-year symptomatic, endoscopic and/or radiologic improvement (CT or MRI). Improved endoscopic appearances were classed as reduction in Mayo scores by ≥1 for ulcerative colitis (UC) or CDEIS scores of ≥2 in Crohn's disease (CD). Results: In total, 183 patients (average age 37.5 years, range 16–75, 91 females) met the inclusion criteria. Of these, 87 (47.5%) made up the early group (average age 36.6 years, range 16–75) and 96 patients (52.5%) were included in the late group (average age 38.2 years, range 16–74). There were no significant differences between the two groups in terms of age, sex, subtype of disease, type of biological therapy and percentage on steroids and/or immunomodulators at commencement of biologic. There was a significant association between delayed administration of biologics and no improvement in endoscopic or radiological appearances at 1 year (48.6% vs. 30%, OR 2.2, 95% CI 1.1–4.4, p = 0.03). Delayed receipt of biologics was also associated with worsening gastrointestinal symptoms at 1 year (30.4% vs. 15.2%, OR 2.4, 95% CI 1.1–5.3, p = 0.03). There was no significant association between delayed biologic administration and hospital admissions over the next year, surgery in the following 3 years or primary non-response rates (OR 0.89; p = NS; OR 1.1; p = NS; OR = 1.5; p = NS, respectively). Conclusions: In the outpatient setting, delay in biologic administration may affect improved rates of symptomatic improvement and endoscopic/radiological appearances at 1 year. Efficient mechanisms for timely biologic administration are needed to mitigate against the delay caused by increasing referrals, lack of capacity on infusion units and funding applications.